Characterizing rhizosphere microbial communities associated with tolerance to aboveground herbivory in wild and domesticated tomatoes - Tronson, Emily; Kaplan, Ian; Enders, Laramy (Frontiers in Microbiology, 2022)
Root-associated microbial communities are well known for their ability to prime and augment plant defenses that reduce herbivore survival or alter behavior (i.e., resistance). In contrast, the role root microbes play in plant tolerance to herbivory, an evolutionarily sustainable alternative to resistance, is overlooked. In this study, we aimed to expand our limited understanding of what role rhizosphere microbial communities play in supporting tolerance to insect damage. Using domesticated tomatoes and their wild ancestors (Solanum spp.), we first documented how tobacco hornworm (Manduca sexta) herbivory impacted tomato fruit production in order to quantify plant tolerance. We then characterized the bacterial and fungal rhizosphere communities harbored by high and low tolerance plants. Wild tomatoes excelled at tolerating hornworm herbivory, experiencing no significant yield loss despite 50% leaf area removal. Their domesticated counterparts, on the other hand, suffered 26% yield losses under hornworm herbivory, indicating low tolerance. Ontogeny (i.e., mid- vs. late-season sampling) explained the most variation in rhizosphere community structure, with tomato line, tolerance, and domestication status also shaping rhizosphere communities. Fungal and bacterial community traits that associated with the high tolerance line include (1) high species richness, (2) relatively stable community composition under herbivory, and (3) the relative abundance of taxa belonging to Stenotrophomonas, Sphingobacterium, and Sphingomonas. Characterizing tolerance-associating microbiomes may open new avenues through which plant defenses are amended in pest management, such as plant breeding efforts that enhance crop recruitment of beneficial microbiomes.